Exploration of Mulan's Employment of Masculine Language in Mulan (Disney 1998) - Liao, Yiyang (Journal of Ecohumanism, 2025)
This paper examines the unique employment of masculine language by the character Mulan in Disney's 1998 film Mulan, underpinning its analysis with Judith Butler’s theory of gender performativity. Unlike traditional Disney princesses, Mulan adopts a non-stereotypical female role by disguising herself as a male warrior to save her country. With a conversation analysis approach, this study delves into how Mulan's language reflects masculinity, thereby challenging conventional gender roles and contributing to her portrayal as a formidable war hero. Using a sociolinguistic framework by scholars Tannen, Coates, and Mills, the paper analyses seven conversations from the film to reveal how Mulan’s speech aligns with masculine constructs such as assertiveness, independence, and dominance. The findings of this paper not only support Butler's notion that gender is performative but also highlight the media’s role in shaping and challenging societal norms concerning gender.